Effects of Y incorporation in TaON gate dielectric on electrical performance of GaAs metal–oxide–semiconductor capacitor. Issue 9 (29th August 2016) - Liu, Li Ning; Choi, Hoi Wai; Xu, Jing Ping; Lai, Pui To
Abstract : In this study, GaAs metal–oxide–semiconductor (MOS) capacitors using Y‐incorporated TaON as gate dielectric have been investigated. Experimental results show that the sample with a Y/(Y + Ta) atomic ratio of 27.6% exhibits the best device characteristics: high k value (22.9), low interfacestate density (9.0 × 10 11 cm –2 eV –1 ), small flatband voltage (1.05 V), small frequency dispersion and low gate leakage current (1.3 × 10 –5 A/cm 2 at V fb + 1 V). These merits should be attributed to the complementary properties of Y2 O3 and Ta2 O5 :Y can effectively passivate the large amount of oxygen vacancies in Ta2 O5, while the positively‐charged oxygen vacancies in Ta2 O5 are capable of neutralizing the effects of the negative oxide charges in Y2 O3 . This work demonstrates that an appropriate doping of Y content in TaON gate dielectric can effectively improve the electrical performance for GaAs MOS devices.Capacitance–voltage characteristic of the GaAs MOS capacitor with TaYON gate dielectric (Y content = 27.6%) proposed in this work with the cross sectional structure and dielectric surface morphology as insets. Abstract : Y incorporating into TaON gate dielectric is investigated to be capable of improving the interfacial and gate leakage properties of GaAs MOS devices due to the combination of the advantages of Ta2 O5 and Y2 O3 high‐ k materials. An optimum Y concentration in TaYON dielectric that achieves a high k value close to TaON and two‐order lower gate leakage current than TaON devices is obtained.Capacitance–voltage characteristic of the GaAs MOS capacitor with TaYON gate dielectric (Y content = 27.6%) proposed in this work with the cross sectional structure and dielectric surface morphology as insets.